The acute effects of cycling on running kinematics - Gottschall, J. S.; Palmer, B. M. (Medicine & Science in Sports & Exercise, 1997)
The effects of an intense bout of cycling on ensuing running kinematics were investigated. Speed, heart rate, and perceived exertion were also measured. This study has relevance for triathlon and cross-training. Male triathletes (N = 10) completed two trials on separate days. First, a 30-min high-intensity effort on a windtrainer was immediately followed by a 5 km run. Second, Ss completed a 30-min run at the same heart rate as that measured during the cycling bout in the first trial, and then immediately followed with a 5 km run. After the cycling bout, Ss ran with a shorter stride length and a higher stride frequency, heart rates were higher, and the rating of perceived exertion was lower. Implication: This investigation demonstrates the negative effects of cycling on running performance. Although this effect cannot be removed in a triathlon event, it does demonstrate a detrimental effect for cross-training advocates. The value of cycling for running performance must be questioned for uses other than exercising while injured or if done at low intensity levels as general active recovery.